Performative pedagogies: feeling the experience of being (the) social in twenty-first century learning. Issue 3 (2nd July 2020) - Trezise, Bryoni
ABSTRACT: This article explores the application of theatre and performance pedagogies to broader contexts of interdisciplinary teaching and the increasingly diversified student body. It further attends to the affective dimensions of the twenty-first century digital classroom. In doing so, it proposes that a pedagogy of 'meta-affect' opens out the capacity for students to become critically aware of how socialities of the digital classroom are built through affect. It draws on German-based collective Rimini Protokoll's Remote X to show how performative visualisations of the smooth affects of digital culture enable for the development of students' capacities to conceptualise models of real-world change.